TEX: The New Insensitive High Explosive - Talwar, M. B.; Nair, J. K.; Palaiah, R. S.; Mukundan, T.; Singh, Haridwar (Defence Science Journal, 2002)
Insensitive high explosive 4, 10-dinitro-2,6,8, 12-tetraoxa-4, 10-diazatetracyclo (5.5.0.0.5,9 03,11) dodecane (TEX) has been synthesised by an improved laboratory-scale process using 93 per cent to 96 per cent nitric acid as nitrating agent. Characterisation of the product was done based on its physical constants, infrared, differential thermal analysis, and mass spectral studies. Explosive and ballistic parameters of TEX containing formulations were computed using Becker-Kistiakowsky-Wilson (BKW) code and NASA Chemical Equilibrium Composition- 71 programme, respectively. Semi-empirical quantum mechanical calculations using the parametric model 3 (PM3) method have been carried out for the TEX molecule. The optimised geometrical parameters and heats of formation were obtained from semi-empirical PM3.